2024
DOI: 10.3389/fpls.2023.1284781
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for target traits in the Australian lentil breeding program

Alem Gebremedhin,
Yongjun Li,
Arun S. K. Shunmugam
et al.

Abstract: Genomic selection (GS) uses associations between markers and phenotypes to predict the breeding values of individuals. It can be applied early in the breeding cycle to reduce the cross-to-cross generation interval and thereby increase genetic gain per unit of time. The development of cost-effective, high-throughput genotyping platforms has revolutionized plant breeding programs by enabling the implementation of GS at the scale required to achieve impact. As a result, GS is becoming routine in plant breeding, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Several studies on various crops have shown that genomic prediction and selection hold the potential to increase e ciency, allowing not only the optimization of existing resources, but also the reduction of the preceding requirements (Duangjit et al 2016;Matei et al 2018;Gebremedhin et al 2024). Adopting this methodology will reduce the cost of genotyping, allow the development and use of statistical models capable of tting genome-wide marker data, and the increase data processing capacity (Wartha and Lorenz 2021; Covarrubias-Pazaran 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on various crops have shown that genomic prediction and selection hold the potential to increase e ciency, allowing not only the optimization of existing resources, but also the reduction of the preceding requirements (Duangjit et al 2016;Matei et al 2018;Gebremedhin et al 2024). Adopting this methodology will reduce the cost of genotyping, allow the development and use of statistical models capable of tting genome-wide marker data, and the increase data processing capacity (Wartha and Lorenz 2021; Covarrubias-Pazaran 2022).…”
Section: Introductionmentioning
confidence: 99%